The Attitudes of Pedestrians when Using Crosswalks with Distinct Traffic Lanes: A Case Study on Chaeng Watthana Road, Lat Krabang Road, and Kingkaeo Road - Veerapong Booncharoenpanya; Jumrus Pitaksringkarn (Engineering and Technology Horizons, 2024)
One of the most important modes of transportation in cities and suburbs is walking. In large urban areas, walking reduces traffic congestion. However, data indicates that Bangkok is responsible for 1 in 3 pedestrian accidents per year, with an average of 900 such incidents taking place there. Furthermore, based on data collected from 2013 to 2017, car-pedestrian collisions are categorized by the highest severity index due to the average of 55 fatalities per 100 accidents. These statistics show that there are, on average, 740 pedestrian-vehicle incidents annually. The data indicates that to lower the number of pedestrian fatalities, walking mode needs to be enhanced. Consequently, the investigator was interested in determining how crossing facilities and people's attitudes are related. The goal of this research is to examine significant variables that influence how pedestrians feel about crossing the street. A questionnaire was used to collect data, which was separated into two sections: attitude about crossing the road and attitude regarding safety when crossing the road. The study's sample crosswalks are located on Chaeng Watthana Road, Lat Krabang Road, and King Kaew Road. Descriptive statistics and linear regression were employed in the analysis to consider social characteristics, variables related to past road crossing experience, variables regarding attitudes toward using road crossings, and variables regarding crossing facilities. Results from 412 questionnaires show that the number of traffic lanes, vehicle volume and vehicle speed were determined to be the primary factors significantly reducing the attitude of security that one feels when crossing the street. Furthermore, the outcomes held up when descriptive statistics were used for analysis. It was discovered that push-button traffic lights had the biggest influence on attitudes of safety when it came to attitudes regarding crossing facilities.
Keywords: Urban Transport and Accessibility; Evacuation and Crowd Dynamics; Traffic and Road Safety